2019
DOI: 10.3390/molecules25010160
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Anthraquinones, Iridoid Glycosides and Triterpenoids in Morinda officinalis and Morinda citrifolia Using UPLC/Q-TOF-MS and Multivariate Statistical Analysis

Abstract: Roots of Morinda officinalis and Morinda citrifolia have been interchangeably used in traditional Chinese medicine. However, there is no experimental evidence to support this. In this study, a ultra-performance liquid chromatography quadrupole time-of-flight mass spectrometry (UPLC/Q-TOF-MS)-based approach and a multivariate statistical analysis (MSA) were adopted to compare the difference in the chemical compounds present in the root extract of M. officinalis and M. citrifolia. There were 26 anthraquinones, 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
0
24
0
1
Order By: Relevance
“…Various doses have been used for testing the effects of Noni [ 25 , 28 , 35 ]. The toxicological studies revealed that higher doses of Noni fruit juice of 4000 mg/kg or 5000 mg/kg for two or more months may cause toxic effects on the liver and kidneys [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Various doses have been used for testing the effects of Noni [ 25 , 28 , 35 ]. The toxicological studies revealed that higher doses of Noni fruit juice of 4000 mg/kg or 5000 mg/kg for two or more months may cause toxic effects on the liver and kidneys [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Doses of 500–1000 mg/kg of Noni extract produced heptoprotective effects, proven by an increase in the liver antioxidant enzyme and alkaline phosphatase activity [ 25 ]. For in vitro experiments, 0.4, 1.2, 3.7, 11.1, 33.3 and 100 µg/mL concentrations were used to perform cell viability assays [ 35 ]. Researchers have applied the concentrations of 25, 50 and 100 µg/mL for the cell colony-formation assays [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PCA and PLS-DA are mathematical approaches that can be applied to chemical or biological data, in order to recognize pattern and classify the samples, and the two methods have been widely used in discriminating and comparing the composition of herbal medicines [ 17 , 18 , 19 ]. To provide more information about the chemical differences and find potential chemical markers which contributed to the differences among flowers, leaves, and roots of TM, PCA and PLS-DA were further carried out.…”
Section: Resultsmentioning
confidence: 99%
“…Galioside (3) were reported for the first time from Morinda genus. Compounds, asperulosidic acid (1), [12] geniposidic acid (2), [13] 2-hydroxymethyl-3-hydroxyanthraquinone (4), [4] rubiadin-1-methyl ether (5), [12] and anthragallol-2methyl ether (6) [14] were already reported from M. officinalis.…”
Section: Extraction and Isolationmentioning
confidence: 99%